The impact of digital technology use on farmers’ low-carbon production behavior under the background of carbon emission peak and carbon neutrality goals - Huang, Xiaohui; Yang, Fei; Fahad, Shah (Frontiers in Environmental Science, 2022)
In the digital economy era, as a new production factor, digital technology can break through the information blocking constraints on farmers’ behavior, become an important driving force affecting farmers’ low-carbon production behavior, and provide new opportunities for agricultural green low-carbon transformation and the realization of carbon emission peak and carbon neutrality goals. Based on the field survey data of 571 farm households in Jiangsu Province, China, this paper employs the Ordered Probit model and the mediating effect test method, and takes risk cognition as the mediating variable to empirically analyze the impact of digital technology use on farmers’ low-carbon production behavior and its path. The study results show that environmental risk cognition, health risk cognition, agricultural product safety risk cognition, and pesticide residue risk cognition have a significant positive impact on farmers’ low-carbon production behavior. Study findings also reveal that, on one side, the use of digital technology has a direct effect on the farmers’ low-carbon production behavior, on the other side, it indirectly affects the farmers’ low-carbon production behavior by affecting their risk cognition, that is, risk cognition plays a partial mediation role in this relationship. Furthermore, the results indicate that among the control variables, joint cooperative membership, food security knowledge, agricultural income, technical guidance, and following instructions have a significant and positive impact on farmers’ low-carbon production behavior. Based on study findings, the variable “number of the labor force” has a negative and significant impact on farmers’ low-carbon production behavior. Based on study findings, to effectively realize carbon emission peak and carbon neutrality goals and promote sustainable and high-quality agriculture development, agricultural policy makers should pay attention to the role of digital technology to actively promote low-carbon production behavior.